2022
DOI: 10.1001/jamacardio.2022.2584
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Imaging and Targeted Therapies for Recurrent Pericarditis

Abstract: ImportancePericarditis is the most common form of pericardial disease. Recurrence of pericarditis affects 15% to 30% of patients after the initial episode of pericarditis. Up to 50% of patients with the first recurrence have additional recurrences. These patients often progress to have colchicine-resistant and corticosteroid-dependent disease. Rapidly evolving cardiac magnetic resonance imaging techniques and novel targeted therapies have paved the way for imaging-guided therapy for recurrent pericarditis. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 103 publications
(166 reference statements)
0
3
0
2
Order By: Relevance
“…An additional important point deals with patients’ phenotyping in order to provide a tailored therapy. Recent studies identified a central role for CMR in the diagnosis of acute pericarditis (e.g., LGE sequence and edema-weighted T2-weighted short-tau inversion recovery sequence) in patients experiencing multiple recurrences [ 34 , 38 , 86 ]. CMR can be coupled with the measurement of inflammatory biomarkers to recognize patients at higher risk for complications [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional important point deals with patients’ phenotyping in order to provide a tailored therapy. Recent studies identified a central role for CMR in the diagnosis of acute pericarditis (e.g., LGE sequence and edema-weighted T2-weighted short-tau inversion recovery sequence) in patients experiencing multiple recurrences [ 34 , 38 , 86 ]. CMR can be coupled with the measurement of inflammatory biomarkers to recognize patients at higher risk for complications [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Назначение анакинры следует обсуждать в первую очередь у пациентов с ИРП, резистентных к терапии НПВП и колхицином (острый перикардит -3 мес., первый рецидив в пределах 6 мес. ), имеющих увеличение концентрации СРБ и/или признаки воспаления перикарда по данным МРТ [1,94]. По данным исследования IRAP [128], введение анакинры в дозе 100 мг/сут.…”
Section: Discussionunclassified
“…Общие подходы к фармакотерапии перикардита, включающие применение НПВП, колхицина, ГК и иммуносупрессивных препаратов, рассмотрены в серии обзоров [91][92][93][94][95]. Особое внимание в последние годы привлечено к ГИБП, механизмы действия которых направлены на блокирование связывания ИЛ-1 с рецептором ИЛ-1 (анакинра) или эффектов самого ИЛ-1 (канакинумаб и рилонацепт) [96][97][98].…”
Section: применение анакинры при перикардитеunclassified
“…Alternative treatments proposed for this disorder were steroid-sparing agents; however, strong data on their overall efficacy are lacking [ 1 , 30 , 31 , 32 ]. Fortunately, the introduction of interleukin-1 (IL-1) blockers in the present decade constituted a paradigm shift towards the targeted therapy of colchicine-resistant glucocorticoid-dependent recurrent pericarditis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%